A Review of Strategies for Improving 3-Phase Induction Motor Performance - Zuriman Anthony; Refdinal Nazir; Muhammad Imran Hamid (Andalasian International Journal of Applied Science, Engineering and Technology, 2024)
The 3-phase induction motor is an electric motor with a strong, reliable, and easy-to-operate construction, and it is cheaper compared to other types of electric motors, making it widely used by the public. Although this motor is considered reliable, it still has some drawbacks, such as low performance, including starting torque, power factor, and efficiency compared to other types of electric motors. Therefore, research to improve the performance of this motor is ongoing. This paper aims to outline some methods that have been used by previous researchers to improve the performance of induction motors based on literature studies. Some of the methods discussed in this paper include the use of permanent magnets on the rotor, operating the 3-phase induction motor on a single-phase system, developing ferromagnetic materials for the motor, increasing the number of coil phases, and optimizing coil design in the motor. The advantages and disadvantages of using these methods to improve motor performance are briefly outlined.